The Role of Mindfulness in Improving Learning Concentration: A Qualitative Study in Secondary Education Environment - Rahmawati Putri Rahayu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Learning concentration is one of the important factors that determine learning success. This study aims to examine the role of mindfulness in improving learning concentration in secondary education students. This research uses a qualitative approach with a case study method. The research subjects were 10 secondary education students who participated in an 8-week mindfulness program. Data were collected through in-depth interviews, observation, and documentation. The results show that mindfulness can improve students' learning concentration in two ways, namely: (1) Increasing awareness of thoughts and feelings. (2) Improve the ability to manage thoughts and feelings. Based on the results of this study, mindfulness is an important skill to be developed by students in a secondary education environment. The development of mindfulness skills can be done through various activities, such as meditation, yoga, and breathing exercises.